China : Air, Land, and Water - Environmental Priorities for a New Millennium - World Bank (Washington, DC, 2013)
This report represents a further chapter in the dialogue between the World Bank and the People's Republic of China about how to promote economic growth and protect China's environment. There are three cross-cutting issues that keep recurring throughout the analysis. These issues characterize the environmental management challenge over the next decade: First, the environmental agenda is becoming so complex and large that it cannot be adequately managed by one agency--the State Environmental Protection Administration (SEPA) and its counterparts at lower levels--working on its own. Effective solutions will require the combined and coordinated efforts of many different branches of government and the re-thinking of many development policies. Second, the systemic fiscal and budgetary problems facing the country as a whole are making it difficult for environmental institutions to do their work. There is a growing gap between assigned responsibilities and the resources provided to carry out those responsibilities. Third, the government has to continue to diversify the approaches it takes and the environmental tools it uses to provide a better fit between the solutions developed and the problems being experienced in different parts of the country. The "one-size-fits-all" approach, as exemplified by various mass environmental campaigns, played a useful role in the past, but is proving increasingly inadequate to meet current demands.